(untitled) (Journal of Asian Development Studies, 2024)
This article looks at the norms of turn-taking in Urdu discourse as an aspect of female communication tactics. A "turn-talking game" is what Tannen (1984) describes communication as being. This study aims to discover the structure of female turn-taking patterns in Urdu conversations and the distribution of turns within them. While the data does demonstrate that speakers switch and turn size and ordering might fluctuate, the majority of the time, just one side is speaking at a time. Different methods are employed to distribute turns, and those transitions are meticulously coordinated. The research also considers overlapping and pauses in Urdu conversation, but they do not distort the turn-taking pattern. Instead, these elements are ruled preserving.